(untitled) (PYC Nepal Journal of Management, 2012)
The article evaluates the performance of Bhrikuti Paper and Pulp Nepal (BPPN) Ltd. through the Ex-post Facto Analysis by taking different indicators and variables based on secondary data. It used ratios, average and percentage. The study showed no contribution of privatization in the improvement of performance indicating privatization is not the only one end for improvement.